2016
DOI: 10.4314/ahs.v16i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Plasma inflammatory biomarkers response to aerobic versus resisted exercise training for chronic obstructive pulmonary disease patients

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a main risk for morbidity, associated with alterations in systemic inflammation. Recent studies proved that morbidity and mortality of COPD is related to systemic inflammation as it contributes to the pathogenesis of atherosclerosis and cardiovascular disease. However, increase of inflammatory cytokines adversely affects quality of life, alteration in ventilatory and skeletal muscles functions. Moreover, exercise training has many beneficial effects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 50 publications
0
22
1
Order By: Relevance
“… 100 , 101 In general, longer periods of regular exercise training show a decrease of many inflammatory cytokines such as TNF-α, IL-2, IL-4, and CRP in COPD patients. 102 Similarly, in murine models, a reduced expression of cell surface markers on circulating immune cells such as vascular adhesion molecule-1 (VCAM-1), ICAM-1, and CD62L was shown after regular treadmill running. Also several other inflammatory cytokines such as IL-1α, MCP-3, MIP-1β, MIP-1α, and CD40L were shown to decrease in smoke-exposed mice after training.…”
Section: Immune-regulating Effects Of Exercise Trainingmentioning
confidence: 97%
“… 100 , 101 In general, longer periods of regular exercise training show a decrease of many inflammatory cytokines such as TNF-α, IL-2, IL-4, and CRP in COPD patients. 102 Similarly, in murine models, a reduced expression of cell surface markers on circulating immune cells such as vascular adhesion molecule-1 (VCAM-1), ICAM-1, and CD62L was shown after regular treadmill running. Also several other inflammatory cytokines such as IL-1α, MCP-3, MIP-1β, MIP-1α, and CD40L were shown to decrease in smoke-exposed mice after training.…”
Section: Immune-regulating Effects Of Exercise Trainingmentioning
confidence: 97%
“…In 2010, Van der Vlist et al (van der Vlist and Janssen, 2010 ) conducted a literature review and concluded that endurance or resistance training showed beneficial effects on physical parameters in COPD, despite the absence of any decrease in inflammatory mediators. In 2016, Abd El-Kader et al ( 2016 ) compared the response of inflammatory cytokines after aerobic vs. resistance training and showed that mean values of TNF-α, IL-2, IL-4, IL-6, and C-reactive protein (CRP) were significantly reduced in both groups after 12 weeks of exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…All studies found that pulmonary rehabilitation programs or individual physical therapy programs were effective in improving the quality of life [12][13][14][15][16][17], physical endurance [12][13][14][15][16][18][19][20][21][22][23], respiratory muscle strength [13,18,23], reducing symptoms of CoPd [14,16,19,23], improving the function of external breathing [16,[24][25][26], blood parameters [22,27], cognitive functions [21], functional state of muscles [28], survival rates [29,30], and reducing the number of hospital days [31]. The main part of investigations was devoted to the comparison of therapeutic rehabilitation programs that included several components and referred to stable patients with CoPd.…”
Section: Resultsmentioning
confidence: 99%